2018
DOI: 10.3126/njn.v15i3.23280
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Outcome Differences among the Ischemic Stroke Subtypes basedon TOAST Classificationat Tribhuvan University Teaching Hospital, Nepal

Abstract: The objective of this study was to explore the outcome differences among is chemic stroke sub types based on “Trial of ORG 10172 in Acute Stroke Treatment (TOAST)” system in a tertiary referral hospital. A hospital based prospectiv elongitudinal study was conducted involving 182 patients. Modified Rank in Scale (MRS) was used to assess functional out come, Kaplan-Meierproduct- limit method and Coxproportional hazards regression analys is were used to evaluate rates and identify predictors of survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…As indicated in Table 1 , the pooled mean age was 62.4 years, ranging from 51.9 [ 38 ] to 70.5 years [ 18 ]. From 46 studies reporting data on sex distribution, 44 studies showed a higher percentage of stroke in males [ 10 , 12 – 14 , 16 , 19 – 21 , 23 28 , 30 – 33 , 35 – 41 , 43 45 , 47 51 , 53 – 59 , 61 – 64 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As indicated in Table 1 , the pooled mean age was 62.4 years, ranging from 51.9 [ 38 ] to 70.5 years [ 18 ]. From 46 studies reporting data on sex distribution, 44 studies showed a higher percentage of stroke in males [ 10 , 12 – 14 , 16 , 19 – 21 , 23 28 , 30 – 33 , 35 – 41 , 43 45 , 47 51 , 53 – 59 , 61 – 64 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From 23 studies investigating aspects of acute care [ 13 , 30 , 40 , 49 ], four studies consisted of data on length of hospital stay [ 13 , 30 , 40 , 49 ], four studies highlighted complications [ 13 , 16 , 30 , 48 ], and 19 studies reported mortality [ 11 , 17 , 21 , 26 , 29 , 30 , 32 , 34 , 36 , 38 , 40 , 41 , 45 , 48 , 51 , 52 , 56 , 57 , 62 ]. 12 studies included treatment modalities [ 21 , 31 , 32 , 36 , 38 , 42 45 , 48 , 57 , 61 ] [ 42 , 44 , 61 ].The outcome of stroke was described in 22 studies [ 11 , 17 , 21 , 26 , 29 , 30 , 32 34 , 36 , 38 , 40 , 41 , 43 45 , 48 , 51 , 52 , 56 , 57 , 62 ], and the long-term outcome (3 months after stroke) was investigated only in seven studie...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations